Conservation management practice for the Malaysia Heritage Trust (Badan Warisan Malaysia) [compact disc] - 324003 Mukram Idris (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2005